Go virtual: exploring augmented reality application in representation of steel architectural construction for the enhancement of architecture education - Abdullah, Fadzidah; Kassim, Mohd Hisyammudin; Sanusi, Aliyah Nur Zafirah (American Scientific Publishers, 2017)
This research explores the application of Augmented Reality (AR) in architecture education, specifically focusing on students’ understanding of steel architectural construction. The research has the following objectives: to reconstruct virtual 3D construction steel details with AR application, to analyze students’ feedback on their explorative learning experience and to examine their satisfaction in the learning method introduced using AR application. This research is conducted using qualitative and quantitative approach. Primary data is obtained by letting students to reconstruct 3-D modelling of steel architectural details and their AR prototypes, and by obtaining students’ feedback via questionnaire survey. Secondary data is obtained by literature review in relation to background studies of AR technology advancement. The results show that 87% of the students agreed the assignment offers great experience in learning. Furthermore, 79% of the respondents were satisfied with the learning by experience. This study contributes to the provision of knowledge on the advancement of Augmented Reality (AR) applicable in Architecture education, in particular, steel construction information and development.